A promoção do engajamento das famílias no Programa Criança Feliz - Marini, Bruna Pereira Ricci (2023)
Strategies for care and promotion of childhood development have evolved substantially over the last century. In this context, Early Intervention with a Family-Centered Approach has emerged in terms of effectiveness, evidence-based and quality interventions, taking part in the list of those currently recognized as recommended practices. Studies have shown that the engagement of families is a decisive component to achieve the expected results in this care model, since they are expected to participate and strengthen their knowledge, skills and beliefs of self-efficacy in caring for children. Despite its importance, this is still a briefly studied element. In Brazil, the launch of the Programa Criança Feliz (Happy Child Program) produced an approximation with this intervention model; however, its results are still measured only by the outcome in children. Thus, this study aims to elucidate the strategies adopted in Programa Criança Feliz, a program of home visits with an approach to promote the engagement of families with children up to six years old, with disabilities and/or exposed to a situation of vulnerability and social risk. This is a cross-sectional, descriptive and exploratory study, with a qualitative approach, developed in four steps. Step 1: analysis of the incorporation of strategies aimed at family engagement in the decrees, ordinances and theoretical instruments that build up the reference for the training of visitors; Step 2: exploratory study with coordinators and supervisors of Programa Criança Feliz; Step 3: exploratory study with visitors from Programa Criança Feliz; Step 4: exploratory study with families part of Programa Criança Feliz. The sample was selected in a non-probabilistic way and for convenience, being composed of two coordinators, three supervisors, seven visitors and five families who take part in Programa Criança Feliz in the municipalities belonging to the Regional Direction of Social Assistance and Development of Araraquara, state of São Paulo. nData from the first step of the study was collected from documents and materials that support the training of program visitors. In the second, third and fourth steps, data collection was carried out through semi-structured interviews with coordinators, supervisors, visitors and families. Data analysis was carried out using the content analysis technique, in thematic analysis mode. The results of the study allowed us to verify that family engagement is a construct approached indirectly in the context of the Programa Criança Feliz, since there is little evidence on how it is promoted and how it impacts on other actions developed. Aspects related to the structure and implementation of the program were identified as producing negative impacts on engagement, as well as social vulnerability and its consequences on family conditions. Even so, elements were identified that favor and direct the outcomes of behavioral, cognitive and emotional involvement that build up the motivational structure of engagement, in addition to relational practices that were considered of great importance for this process. Thus, the study points out that there are still gaps in the Programa Criança Feliz proposal, which are related not only to the conditions of engagement, but to previous issues, such as the need to strengthen policies that focus on guaranteeing fundamental rights, aimed at strengthening families' care conditions for their children.